Dual targeting of TAM receptors Tyro3, Axl, and MerTK: Role in tumors and the tumor immune microenvironment - Kai-Hung Wang; Dah-Ching Ding (Tzu Chi Medical Journal)
In both normal and tumor tissues, receptor tyrosine kinases (RTKs) may be pleiotropically expressed. The RTKs not only regulate ordinary cellular processes, including proliferation, survival, adhesion, and migration, but also have a critical role in the development of many types of cancer. The Tyro3, Axl, and MerTK (TAM) family of RTKs (Tyro3, Axl, and MerTK) plays a pleiotropic role in phagocytosis, inflammation, and normal cellular processes. In this article, we highlight the cellular activities of TAM receptors and discuss their roles in cancer and immune cells. We also discuss cancer therapies that target TAM receptors. Further research is needed to elucidate the function of TAM receptors in immune cells toward the development of new targeted immunotherapies for cancer.